Zagadnienie nierówności społecznej w "De Gubernatione Dei" Salwiana z Marsylii : aspekty prawne - Wójcik, Monika (Prawo Kanoniczne, 2011)
Salvian both recognized and censured social inequality, however, without transposing his critical attitude onto the relationship between freemen and slaves. For Salvian, this relationship was a point of reference, though indirect, to the relationship between man and God. Salvian considered the characteristics commonly attributed to slaves against the backdrop of Christian duties before God. When it comes to the situation of slaves, some Salvian’s opinions on the lord’s ius vitaenecisque are in conflict with the existing law, as, for instance, some provisions safeguarding slaves against owners’ abuse or lawlessness. Yet, such provisions might not have been fully observed in practice. Salvian recognizes some undeniable Roman flaws when examining the issue of exploitation of the poor by the rich. The main Salvian’s objections relate to both excessive financial burden laid on citizens by the state, as well as to the wealthy shifting the tax encumbrance to the needy. State legislation took some measures to remedy this situation, but, as follows from Salvian’s account, these regulations remained a dead letter. Salvian repeatedly touches on the problem of the ineffective state apparatus. In Salvian’s opinion, in the aftermath of the unjust state financial system, many Roman citizens fled to become the subjects of the barbarian rule. Salvian attributed ill intentions and oppression of the poor to the councillors; it was largely due to their tax collection powers. As follows from Salvian’s account, the councillors’ assumption of the function of tax collectors was to the significant detriment of social relations in cities. The author briefly reviews their role with the maxim: quot curiales, tot tyranni. Not infrequently, Salvian’s considerations seem rather selective, particularly with respect to the socio-political situation. In his opinion, the Roman Empire of the 5th century faced a dramatic economic slump, first, due to the barbarian invasions, and second, due to the poor administration.